Equvalent Issues in Translating Proverbs and the Strategies used - Astiari, Komang; Suardana, I Putu Eka (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
This study investigated some equivalent issues in translating English proverbs into Indonesian and strategies applied to deal with it. As proverbs are statement that consist of moral value and traditional views to describe situation in daily life, several properties between source language and target language are shared. This study explores the constraints translators face when translating English proverbs into Indonesian due to the lack of equivalents. This research uses qualitative methods. Qualitative research is a type of research based on the collection, analysis, and interpretation of data in narrative form. Data collection is done by looking for English proverbs contained in the book "101 American English Proverbs, Understanding Language and Culture Through Commonly Used Sayings" then understanding each meaning of the proverbs. The problems that appear because of non-equivalence and this study found some issues namely culture-specific concept, the SL concept is not lexicalized in the TL, the SL is semantically complex, the source and target language make distinction in meaning, the TL lacks a specific term (hyponym), differences in physical or interpersonal perspective, differences in expressive meaning, and the use of loan words on the SL. Conclusion, strategies need to be applied in translating proverbs namely using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, and translation by paraphrase.